Pembuatan Akta Melalui Telekonferensi: Sebuah Hukum Cyber Notary - Humairah, Syamsi Ayu; Liman, Padma D; Maskun, Maskun (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
This research aims to examine electronic signature arrangements in electronic general meetings of shareholders. and to find out about the proof of the electronically signed deed of the minutes of the general meeting of shareholders. The research was carried out using normative research methods using a statutory approach and a conceptual approach. Analysis of legal materials uses descriptive analysis which is used to solve problems regarding the legal issues to be researched. The research results show that regulations regarding electronic signatures are contained in Article 1 number 12 of the ITE Law which explains that every electronic signature contains verified electronic information in it. And Article 11 of the ITE Law explains that electronic signatures must have legal force and legal consequences that fulfill the requirements stated in that article. And when using an electronic signature, it must be registered and certified so that legal certainty is guaranteed. Regarding the strength of the evidence, this is still doubtful because in the UUJN itself there is no specific regulation regarding the preparation of deeds carried out electronically. In implementing the GMS, the GMS minutes deed use the legal principle of lex specialis derogate legi generali. Lex generalis is Article 16 Paragraph (1) letter m, and lex specialis is the provisions of Article 77 Paragraph (4) UUPT. The legal validity of the deed of the GMS Minutes held via teleconference media still has legal force as an authentic deed and can be used as evidence in court if there are problems in the future.